[Ru(tmphen)3]2[Fe(CN)6] and [Ru(phen)3][Fe(CN)5(NO)] complexes and formation of a heterostructured RuO2–Fe2O3 nanocomposite as an efficient alkaline HER and OER electrocatalyst. Issue 16 (6th April 2022) - Mosallaei, Hamta; Hadadzadeh, Hassan; Foelske, Annette; Sauer, Markus; Amiri Rudbari, Hadi; Blacque, Olivier
Abstract : Heterostructured RuO2 –Fe2 O3 nanocomposite can be viewed as a bi-functional electrocatalyst for HER and OER because it exploits the synergistic effects of heterostructures and active sites at its interface. Abstract : Water electrolysis is one of the most capable processes for supplying clean fuel. Herein, two novel ionic Ru(ii )–Fe(ii ) complexes, [Ru(tmphen)3 ]2 [Fe(CN)6 ] and [Ru(phen)3 ][Fe(CN)5 (NO)], where tmphen = 3, 4, 7, 8-tetramethyl-1, 10-phenanthroline and phen = 1, 10-phenanthroline, were synthesized and characterized by UV-Vis spectroscopy, elemental analysis, FT-IR, and single-crystal X-ray structural analysis. By thermally decomposing the [Ru(tmphen)3 ]2 [Fe(CN)6 ] complex at 600 °C for 4 h, a heterostructured RuO2 –Fe2 O3 nanocomposite was fabricated through a facile one-pot treatment and then characterized by FT-IR, XRD, FT-Raman, UV-Vis (DRS), ICP-OES, FE-SEM, TEM, TGA/DTG, BET, and XPS analyses, which revealed the formation of highly crystalline RuO2 –Fe2 O3 nanoparticles with an average size of 8–12 nm. The prepared nanocomposite was an efficient heterostructured electrocatalyst for performing water-splitting redox reaction processes, including hydrogen and oxygen evolution reactions (HER and OER) in alkaline solutions. In this regard, RuO2 and Fe2 O3 samples were also prepared through thermal decomposition of [Ru(tmphen)3 ](NO3 )2 and K4 [Fe(CN)6 ] precursors, respectively, as control experiments to compare their HER and OER electrocatalytic activity with that of the RuO2 –Fe2 O3 nanocomposite. Specifically, the RuO2 –Fe2 O3 nanocomposite exhibited significant electrocatalytic performance, generating 10 mA cm −2 current density at −148 and 292 mV overpotentials, and the Tafel slope results from fitting the LSV curves to the Tafel equation were −43 and 56.08 mV dec −1 for the HER and OER, respectively. Therefore, the heterostructured RuO2 –Fe2 O3 nanocomposite can be viewed as a bi-functional electrocatalyst for HER and OER because it exploits the synergistic effects of heterostructures and active sites at its interface.